2002
DOI: 10.1177/105382590202500108
|View full text |Cite
|
Sign up to set email alerts
|

Wilderness Writing: Using Personal Narrative to Enhance Outdoor Experience

Abstract: While writing is used to enhance learning in many outdoor programs, it is rarely used as a method for focused self-exploration. A partnership between a recreation professor and a writing teacher provides the training to have both a solid outdoor program and a solid experience in personal narrative in journals and essays. Students participating in such a combined program benefit by a) learning technical outdoor skills and a process of self-discovery, and b) experiencing the complete writing process, and buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 3 publications
(3 reference statements)
0
21
0
Order By: Relevance
“…This process of evaluating circumstance and creating understanding and meaning has been cited as one of the many benefits of outdoor field experiences (Priest & Gass, 1997). Of the many forms of reflection, journal writing has proved to be a popular, yet troublesome, means of processing experience (Anderson, 1992;Bennion & Olsen, 2002;Hammond, 2002;Hettich, 1990;Kerka, 1996).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…This process of evaluating circumstance and creating understanding and meaning has been cited as one of the many benefits of outdoor field experiences (Priest & Gass, 1997). Of the many forms of reflection, journal writing has proved to be a popular, yet troublesome, means of processing experience (Anderson, 1992;Bennion & Olsen, 2002;Hammond, 2002;Hettich, 1990;Kerka, 1996).…”
Section: Introductionmentioning
confidence: 98%
“…As Kerka (1996) noted, "Of course, merely writing in a journal does not automatically ensure critical reflection or other learning outcomes..." (p. 3). As many leisure/ outdoor recreation/education students are encouraged or required to keep journals as part of their coursework, particularly in those courses that have an outdoor field component, it is imperative that students be trained in how to journal effectively (Bennion & Olsen, 2002;Dyment & O'Connell, 2003b;O'Connell & Dyment, 2003). This paper describes the fourth phase of an exploratory study that examined the use of journals in university leisure, outdoor recreation and education courses.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…educators need to be aware of their use of journals as components of academic courses. As we know, journals can be an effective medium for facilitating reflection but are not necessarily and certainly not automatically so (Bennion & Olsen, 2002;Hayman, Wilkes, and Jackson, 2012). Also, when students are simply handed a journal and asked to write about their experiences with little or no structure provided, journals are less effective (Dyment & O'Connell, 2003).…”
Section: Use Of Journals and Structured Reflectionmentioning
confidence: 99%
“…The use of field notebooks is accepted in adventure programming (Bennion & Olsen, 2002;O'Connell & Dyment, 2003), and while some authors have critiqued the method (O'Connell & Dyment, 2003), others have found the usage of field notebooks to increase trust within group situations in the classroom (Grbavac, Piggott, & Rougeux, 2003). Because of their accepted use in adventure programs and their ability to foster increased trust, field notebooks were the primary data source for this study.…”
Section: Data Collectionmentioning
confidence: 99%